Getting more: how to negociate to achieve your goals in the real world - Diamond, Stuart (New York, 2010)
"Negotiation is part of every human encounter, and most of us do it badly. Whether dealing with family, a business, or diplomacy, people often fail to meet their goals in every country and context. They focus on power and "win-win" instead of relationships and perceptions. They don't find enough things to trade. They think others should be rational when they should be dealing with emotions. They get distracted from their goals.